Связь кровососущих мокрецов с сипантропными птицами в условиях Краматорска - Грицай, В.Ф.; Борисова, Н.Ф. (Вестник зоологии, 1973)
The article deals with the data on trophic connection of biting midges of the Culicoides genus with sparows, pigeons and hens under conditions of town of Kramatorsk. The species composition of biting midges and specific weight of the species in collections near the cattle in this town are presented for comparison. 26 species of Culicoides are found on these feeders, the mass species — C. punctatus and C. nubeculosus. 17 species are caught on birds. C. circumscriptus, C. triangulatus, C. obsoletus, C. odibilis and C. reconditus are "established to. prefer birds when choosing the feeders. The character of trophic connections is determined by the peculiarities of biocenoses and by the relations, existing between the feeders and biting midges.